Analisis Implementasi E-Government Dalam Meningkatkan Pelayanan Publik Di Pemerintahan Daerah Kepulauan Riau - Lanjar Sari; Halisa Putri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The implementation of e-government in public services in the Regional Government is expected to produce faster, better, and more efficient public services, and can improve the application of the principles of good governance. In the context of Riau Islands, the implementation of e-government is very important considering the geographical condition of this area which consists of many islands. With e-government, people in Riau Islands can access public services online without having to travel far to the government center. This research aims to analyze the implementation of e-government in improving public services in the Riau Islands regional government. The research method used is a descriptive method with a qualitative approach. Data were collected through interviews with relevant parties, direct observation, and documentation studies. Based on the results of this study, it is recommended that the Riau Islands regional government continue to improve the implementation of e-government by strengthening information technology infrastructure, increasing people’s digital literacy, and conducting regular evaluations of the quality of public services provided through e-government. In addition, cooperation with related parties, both internal and external, also needs to be improved to ensure the success of e-government implementation in improving public services in the Riau Islands regional government.